Board of Directors Diversity and Carbon Emissions Disclosure - Hidayah, Muslikhah Nur; Purnomowati, Nasyiah Hasanah; Cummings, Lorne (Jurnal Akuntansi dan Bisnis, 2024)
The purpose of this study is to examine the effect of board of directors diversity which includes gender, tenure, educational background, and age on carbon emissions disclosure. It is an empirical study of energy sector companies in Southeast Asia from 2017-2021. Sample selection was undertaken by nonprobability sampling using a purposive sampling model. Based on this technique, a sample of 29 companies was obtained with a total of 145 observations that could be used. The analysis method used in this research is multiple linear regression analysis. The results of this study indicate that gender diversity and tenure have a positive effect on the disclosure of carbon emissions. Diversity of educational background does not affect the disclosure of carbon emissions and age diversity has a negative effect on the disclosure of carbon emissions.